Minimum wage, fringe benefits, overtime payments and the gender wage gap - Jo\~ao Cerejeira; Kemal Kızılca; Miguel Portela; Carla Sá (Institute for the Study of Labor (IZA), 2012)
Using linked employer-employee data for Portugal, we explore an amendment to the minimum wage law which increased from 75% to 100% of the full minimum wage applied to employees younger than 18. Our results show a widening of the gender wage gap following the amendment: the wage gap for minors increased 2.7 percentage points more than for other groups. This change was mainly determined by a redistribution of fringe benefits and overtime payments. We discuss three possible sources of redistribution: (i) a change in the skill composition of the working males and females after the increase in the minimum wage, (ii) industrial differences in response to the changes in the wage floor, and (iii) discrimination. Estimations support the second channel as the main contributing factor, while possible discrimination effects cannot be eliminated.
urn:nbn:de:101:1-201206146444
Keywords: J31; J32; J71; 330; minimum wage; overtime payments; fringe benefits; gender wage gap; minors; Mindestlohn; Wirkungsanalyse; Lohndifferenzierung; Betriebliche Sozialleistungen; Überstunden; Schätzung; Portugal